(untitled) (Medicine Today, 2013)
Takayasus arteritis, or pulseless disease is a rare, idiopathic, chronic granulomatous vasculitis that affects aorta and its major branches. This report describes a 57- year-old man who presented with gradual loss of vision, syncopal attack and arm claudication. His ocular findings suggested bilateral ocular ischemic syndrome. He was later diagnosed as having Takayasus disease. DOI: http://dx.doi.org/10.3329/medtoday.v24i2.15013 Medicine Today 2012 Vol.24(2): 79-81